2017
DOI: 10.1088/1741-4326/aa75ee
|View full text |Cite
|
Sign up to set email alerts
|

Microwrinkle structures on refractory metal surfaces irradiated with noble gas plasma species

Abstract: Microwrinkle structures with a pitch of less than 100 nm and up to 600 nm on refractory metals like tungsten (W) and molybdenum, which are irradiated by noble gas ions such as neon and helium, have been studied systematically. The wrinkle formation mechanism is thought to be a buckling of the hard surface layer supported by the soft elastic substrate, which is induced by a penetration of noble gas species from the irradiated surface. Microwrinkle forms on this structure under lateral compressive strain/stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Instead, nitrogen atoms diffused deep into the surface layer and took a pinning role against dislocation movement, leading to the formation of a hard surface layer. This observation is consistent with the buckling model of a hard surface layer supported by soft bulk material, favoring a microwrinkle structure formation [9].…”
Section: Summary and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Instead, nitrogen atoms diffused deep into the surface layer and took a pinning role against dislocation movement, leading to the formation of a hard surface layer. This observation is consistent with the buckling model of a hard surface layer supported by soft bulk material, favoring a microwrinkle structure formation [9].…”
Section: Summary and Discussionsupporting
confidence: 89%
“…Introducing nitrogen gas in deuterium plasmas at a similar surface temperature changed the W surface morphology drastically, as shown in figures 5(b) and (c). The microwrinkle with a pitch of 150-200 nm is clearly observed, similar to these observed in deuterium and Ne mixed-gas discharge plasmas [9]. According to the buckling model of the hard surface layer supported by a soft elastic substrate, nitrogen also seems to contribute the surface hardening.…”
Section: Temperature Dependence Of Surface Morphologysupporting
confidence: 76%
See 1 more Smart Citation
“…The tungsten divertor in ITER will experience massive heat loads (10-20 MW m −2 ) and particle fluxes (10 24 m −2 s −1 ), which can cause significant microstructural and morphological changes [1]. It has been shown that tungsten, under simultaneous implantation to both low energy hydrogen and helium ions within the temper ature range of 1000-2000 K, experiences surface roughening and the formation of a tendril-like fuzz in certain combinations of temper ature and helium fluence [2][3][4]. The formation of this fuzz and other damage effects are especially concerning because they may lead to the formation of high Z dust, as well as enhanced fuel retention [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Whether hydrogen isotopes impinge on materials from the plasma side or diffuse out from the bulk, all particles will interact with the surface. H, in the form of deuterium and tritium isotopes, is the primary fuel source in fusion reactors and will be continuously implanted into the near-surface region of PFCs contributing to deleterious effects such as the formation of bubbles, surface blistering, and changes in the thermal and mechanical properties of the material [1][2][3][4][5][6]. The behavior of hydrogen on various surfaces of tungsten, in particular the (1 1 0) and (1 0 0) surfaces and to a lesser extent the (1 1 1) surface, have been studied both theoretically [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and experimentally [6,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%